LEASING AS AN INSTRUMENT OF MODERNIZATION OF FIXED ASSETS OF HOUSING AND UTILITIES SECTOR - Regina Rakhmatullina (Вестник Северо-Кавказского федерального университета, 2022)
The housing and utilities sector is one of the most important sectors, which raises issues of socioeconomic security of cities and the vital interests of the entire population of the country. To date, utilities has accumulated a large number ofproblems, Central to which is the critical level of depreciation of fixed assets, and lack offunding for their renewal. The development of the industry and providing quality services is impossible without providing industry with innovative resources. The relevance of the research topic due to the urgent need to produce accelerated re-equipment of fixed assets of housing and utilities, and the use of leasing as an effective inancial tool to update it. The article discusses the current state of the housing sector, examines the problem of providing complex utilities basic resources are considered instruments of modernization offixed assets, made conclusions and suggestions on improvement of the development of the industry.